2014
DOI: 10.1371/journal.pone.0112179
|View full text |Cite
|
Sign up to set email alerts
|

Development of Quantitative Proteomics Using iTRAQ Based on the Immunological Response of Galleria mellonella Larvae Challenged with Fusarium oxysporum Microconidia

Abstract: Galleria mellonella has emerged as a potential invertebrate model for scrutinizing innate immunity. Larvae are easy to handle in host-pathogen assays. We undertook proteomics research in order to understand immune response in a heterologous host when challenged with microconidia of Fusarium oxysporum. The aim of this study was to investigate hemolymph proteins that were differentially expressed between control and immunized larvae sets, tested with F. oxysporum at two temperatures. The iTRAQ approach allowed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 96 publications
(112 reference statements)
0
19
0
1
Order By: Relevance
“…Comparing the humoral response to different invading pathogens, gram negative, and gram positive bacteria, Candida, and Fusarium, revealed that the kinetics and grade of up-regulation of lysozyme and different antifungal peptides varies, depending on the class of the infecting agent, indicating that the G. mellonella immune system is able to distinguish between classes of pathogens (Mak et al 2010). Recently, a multiplex proteomic analysis, iTRAQ, was applied to the Galleria model, investigating changes in the expression level of proteins and peptides of larvae challenged with Fusarium conidia (Munoz-Gomez et al 2014). Validations of protein expression by RT-PCR showed that data obtained with iTRAQ were consistent, making it a useful tool for further investigations.…”
Section: Host Immune Response To Infection and Antifungal Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the humoral response to different invading pathogens, gram negative, and gram positive bacteria, Candida, and Fusarium, revealed that the kinetics and grade of up-regulation of lysozyme and different antifungal peptides varies, depending on the class of the infecting agent, indicating that the G. mellonella immune system is able to distinguish between classes of pathogens (Mak et al 2010). Recently, a multiplex proteomic analysis, iTRAQ, was applied to the Galleria model, investigating changes in the expression level of proteins and peptides of larvae challenged with Fusarium conidia (Munoz-Gomez et al 2014). Validations of protein expression by RT-PCR showed that data obtained with iTRAQ were consistent, making it a useful tool for further investigations.…”
Section: Host Immune Response To Infection and Antifungal Agentsmentioning
confidence: 99%
“…The cellular components, haemocytes, are able to phagocytose and kill pathogens by producing reactive oxygen species and lytic enzymes and can be seen as the invertebrate equivalent of neutrophils (Bergin et al 2005). The humoral response to infecting microbes comprehends antimicrobial peptides which were shown to be induced by fungal pathogens, and furthermore differ from those induced by bacterial pathogens (Bergin et al 2006;Munoz-Gomez et al 2014). This explains the comparable data obtained in Galleria virulence studies and murine models (Brennan et al 2002;Slater et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Then prepupae and pupae are formed and, after additional 2 weeks, adult moths appear. This bee moth has been a good model to study insect immune response and virulence factors of many pathogens, including human pathogens such as Pseudomonas aeruginosa , Enterococcus faecalis , Staphylococcus aureus , Candida albicans , Fusarium oxysporum , and Aspergillus fumigatus (Gibreel & Upton, ; Gomez‐Lopez et al ., ; Koch et al ., ; Munoz‐Gomez et al ., ; Maekawa et al ., ; Vaz et al ., ). Their virulence factors can be studied first on the insect model, which is easier, cheaper, and more ethically acceptable, before testing on mammalian organisms (Junquirella, ; Arvanitis et al ., ; Cook & McArthur, ).…”
Section: Introductionmentioning
confidence: 98%
“…Larvae survive in wide range of temperatures (from 25 to 37°C), allowing the simulation of various physiologic conditions. This allows research of a wide range of pathogens, including fungal (Fusarium oxysporum [21,22], Aspergillus fumigatus [23], and Candida albicans [24,25]) and bacterial, such as Staphylococcus aureus (26), Proteus vulgaris (22), Serratia marcescens (27), Pseudomonas aeruginosa (28), Listeria monocytogenes (29), and Enterococcus faecalis (30). In our study, we establish the G. mellonella model for M. abscessus infection.…”
Section: Discussionmentioning
confidence: 99%